Salesforce.com for dummies - Kao, Liz (--For dummies., 2014)
Your fun and easy introduction to Salesforce.com and its latest tools. The frontrunner in the customer relationship management (CRM) market, Salesforce.com has a rapidly expanding influence over the way companies across the globe interact with their clientele. Salesforce.com For Dummies lends you an edge in building those relationships and managing your company s sales, marketing, customer service, and support operations. With this accessible guide, you will learn how to organize contacts, schedule business appointments, use forecasting tools to predict upcoming sales, make accurate projects based on past performance, and more. Covers the latest enhancements to Salesforce.com, the world's most popular customer relationship management software, and explains how to choose the right configuration to suit your business needs; Written by Salesforce.com insiders with years of expertise in CRM services; Details how to personalize your system, prospect leads, manage accounts and partners, develop contacts, track products, calculate forecasts, drive demand, utilize service and support, share insights with Chatter, enhance your online marketing, and more; Close deals faster, gain real-time visibility into sales, and collaborate instantly with help from Salesforce.com For Dummies.--